Bail, Global Justice, and the Limits of Dissent - Esmonde, Jackie (2003)
This article examines the ways in which the law of bail has been used to criminalize dissent in Canada. Three case studies are analyzed to demonstrate how the law of bail has been applied to those arrested at global justice demonstrations associated with militant civil disobedience. The first case study examines the bail conditions imposed on protesters arrested at anti-APEC demonstrations in Vancouver 1997. These bail conditions were intentionally designed to prevent those arrested from attending the protests. The second case study focuses on the Ontario Coalition Against Poverty (OCAP), with an analysis of how the bail system has been used to criminalize its activism through a combination of bail conditions prohibiting public protest, pre-trial detention orders of its leaders, and prohibitions on association with OCAP. The final case study turns to arrests at demonstrations against the Summit of the Americas in Quebec City in April 2001, documenting the intentional violation of the statutory right to a bail hearing within 24 hours, and the denial of bail to a perceived leader of the global justice movement. Viewed together, these case studies demonstrate that the law of bail has provided insufficient protections for civil liberties